Diversity analysis of 80,000 wheat accessions reveals consequences and opportunities of selection footprints - Sansaloni, Carolina P.; Franco, Jorge; Santos, Bruno; Percival-Alwyn, Lawrence; Singh, Sukhwinder; Petroli, Cesar; Campos, Jaime; Dreher, Kate; Payne, Thomas S.; Marshall, David; Kilian, Benjamin; Milne, Iain; et al. (Springer, 2020)
Undomesticated wild species, crop wild relatives, and landraces represent sources of variation for wheat improvement to address challenges from climate change and the growing human population. Here, we study 56,342 domesticated hexaploid, 18,946 domesticated tetraploid and 3,903 crop wild relatives in a massive-scale genotyping and diversity analysis. Using DArTseqTM technology, we identify more than 300,000 high-quality SNPs and SilicoDArT markers and align them to three reference maps: the IWGSC RefSeq v1.0 genome assembly, the durum wheat genome assembly (cv. Svevo), and the DArT genetic map. On average, 72% of the markers are uniquely placed on these maps and 50% are linked to genes. The analysis reveals landraces with unexplored diversity and genetic footprints defined by regions under selection. This provides fertile ground to develop wheat varieties of the future by exploring specific gene or chromosome regions and identifying germplasm conserving allelic diversity missing in current breeding programs.